Pathomorphological Changes of Kidney in Systemic Lupus Erytheis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Systemic lupus erythematosus (SLE) affects people of all races, men and women, but in the latter it dominates and especially often develops in women of reproductive age. The prevalence of SLE among women of reproductive age is 1:500. Almost 90% of lupus patients are women. The reasons for the development of SLE are unknown. It is now generally accepted that gestational complications such as recurrent abortion, preeclampsia and eclampsia, placental abruption, DIC and HELLP syndromes, thrombosis, intrauterine growth retardation, and stillbirth are associated with autoimmune diseases in the mother. The mechanism by which SLE aggravates the course of pregnancy and worsens its outcomes for the mother, fetus, and newborn remains undeciphered. This article analyzes pathomorphological changes in the kidneys in pregnant women with systemic lupus erythematosus. As research materials, the Bukhara Regional Bureau of Pathological Anatomy performed a histological examination of the kidneys obtained at autopsy.